Multiplicity in supervision models: the supervisor’s perspective - van Biljon, J. A.; de Villiers, M.R. (South African Journal of Higher Education, 2016)
Supervision is a vital aspect in the success of postgraduate students and even more so in open distance learning. Various factors influence supervision success, some relating to the student, some to the supervisor and others to the institution. This article addresses an over-arching factor, namely the number of stakeholders involved in a supervision relationship, that is termed multiplicity. The allocation of more than one supervisor has capacity implications which have to be traded against improvements in quantitative success measures and quality factors such as richer pools of knowledge and complementary expertise. This study investigates the perceptions on multiplicity of 22 supervisors who have undertaken supervision in ODL contexts. The research strategy is qualitative, based on an open-ended questionnaire survey and interviews. The main contribution is a set of dimensions, comprising factors that influence postgraduate supervision relationships, and the identification of conditions for considering more than one supervisor.